The Psychometric Properties of the Norwegian version of Swanson, Nolan og Pelham -IV Questionnaire (SNAP-IV) - Kornør, Hege; Bøe, Tormod (PsykTestBarn, 2011)
Description: The SNAP-IV is a questionnaire to assess ADHD symptoms and behaviour problems in school-aged children. It contains 90 items organised in eight scales, and takes less than 30 minutes to complete. James M. Swanson developed the English version in 1983. Geir Øgrim was responsible for the Norwegian translation in 2006. The National Centre for ADHD, Tourette’s syndrome and Narcolepsy is Norwegian copyright holder. Professionals may obtain the scoring key from the centre. There are no other requirements as to the use, scoring or interpretation of the SNAP-IV. Literature search: Our systematic literatures did not identify any studies that addressed the psychometric properties of the Norwegian version of the SNAP-IV. Conclusion: There is no evidence of the psychometric properties of the Norwegian version of the SNAP-IV.